Increased odds of cholangiocarcinoma in Hispanics: results of a nationwide analysis. Issue 1 (January 2020) - Ruiz, Jorge Nicolas; Kröner, Paul T.; Wijarnpreecha, Karn; Corral, Juan E.; Harnois, Denise M.; Lukens, Frank J.
Abstract : Objective: Cholangiocarcinoma (CCA) affects all ethnicities worldwide. The Hispanic population being the leading ethnic minority in the United States, its importance to the healthcare system cannot be understated. This study aims to assess the occurrence and outcomes of CCA in Hispanic patients in the United States. Methods: This is a case-control study using the National Inpatient Sample 2014. All patients with ICD-9 CM codes for CCA were included. Hispanic patients were identified from the ethnic categories within the database. The primary outcomes were the occurrence and odds of CCA in the Hispanic population when compared with other ethnicities. Secondary outcomes were inpatient mortality, morbidity, ICU stay, multiorgan failure, and resource utilization. Results: A total of 13 965 patients with CCA were identified, of which 2750 were propensity-matched to controls (1480 Hispanic). The inpatient occurrence of CCA in Hispanics relative to the national population was 2.73/100 000 persons, compared to 4.82/100 000 persons (39.9/100 000 relative to inpatient population) of all other ethnicities. After adjusting for confounders on multivariate analysis, Hispanic patients displayed adjusted propensity-matched odds of 1.28 ( P < 0.01) of having CCA when compared with other ethnicities. Hispanics did not display different propensity-matched odds of inpatient mortality, morbidity, hospital length of stay, or resource utilization compared to non-Hispanic patients. Conclusion: This study demonstrated that the odds of CCA in admitted patients are higher for the Hispanic population. This difference with the prevalence potentially suggests the presence of social factors such as disparities in cancer prevention or detection in this group.